The development of a methodology using fuzzy logic to assess the performance of cropping systems based on a case study of maize in the Po Valley. (8th July 2013) - Carozzi, M.; Bregaglio, S.; Scaglia, B.; Bernardoni, E.; Acutis, M.; Confalonieri, R.
Abstract The development of tools for evaluating the sustainability of cropping systems is fundamental to providing reliable information on crop performance. In this study, an integrated index [Performance Index (PI)] was developed based on environmental, production and cost variables. In this approach, data are aggregated using a fuzzy logic‐based procedure to deal with the inherent subjectivity at each aggregation step. The PI was tested for three cropping systems in the Po Valley (northern Italy) where maize was grown using minimum tillage, sod seeding and conventional tillage. The methodology proved to be effective for evaluating the three systems. In contrast to other methods for evaluating cropping systems such as those based on agro‐ecological indicators (AEIs), direct aggregation of measured variables reduces the risk of losing information because the level of abstraction in the mathematical formalization of AEIs is usually higher. This advantage is counterbalanced by an increase in the data needed for the evaluation process. The use of domain experts and the mathematical management of subjective decisions should encourage the use of the methodology in other regions and cropping systems.